Astudy on the pathogenicity of Eimeria tenella in village chickens in South Kalimantan - Hamdan, Salfina A; Siswansyah, D.D (Indonesian Journal of Animal and Veterinary Sciences, 1998)
A study on the pathogenicity of various isolates of coccidia (Eimeria tenella) was carved out in village chickens . The isolates were collected from different districts, namely Hulu Sungai Selatan (HSS), Hulu Sungai Tengah (HST), Tapin, and Tanah Laut, South Kalimantan . The result showed that the pathogenicity of E. tenella isolated from two weeks old chickens in HSS district was higher than isolates from the other three districts of the same age of chickens . Further study showed that the isolates of E. tenella from HSS district appeared to cause mortality rates of 64 .3%, 42 .9%, 28 .6%, and 7 .1%, and caecal lesions scores of +4, +3, +2, and +2, in 1, 2, 3, and 4 months old chickens respectively . The body weight gains of the four different age groups of chickens infected with 200,000 oocysts were very significantly lower (P<0.01) than the control group. Â  Keywords: Pathogenicity, Eimeria tenella, village chicken, South Kalimantan